The Quantitative Analysis of Solid Dosage Forms of Itopride using Raman Spectroscopy - Naheed, Iqra; Ehsan, Maida; Nawaz, Haq; Majeed, Muhammad Irfan; Alshammari, Abdulrahman; Albekairi, Norah A.; Ali, Arslan; Ijaz, Tehseen; Saif, Ayesha; Akbar, Haseeb; Aziz, Aleena; Fatima, Rida (Current Pharmaceutical Design, 2026)
ObjectiveThis study explores the application of Raman spectroscopy for identifying and quantifying itopride in solid dosage forms with varying concentrations of active ingredients and excipients. Raman spectroscopy provides a non-invasive, rapid, and accurate detection method that is ideal for pharmaceutical analysis.MethodsThe Raman spectral features of itopride in solid dosage forms were analyzed using Principal Component Analysis (PCA) and Partial Least Squares Regression Analysis (PLS-RA) as multivariate data analysis techniques.ResultsPCA effectively distinguished Raman spectral data of various itopride drug samples. PLS-RA facilitated quantitative analysis, yielding an R2 value of 0.999%, indicating an excellent explanation of model variability. The root mean square error of calibration and prediction were 0.23 mg and 3.02 mg, respectively. Furthermore, PLS-RA accurately determined the active pharmaceutical ingredient concentration in unknown formulations, with a calculated concentration of 79.66/80 mg (w/w) compared to the actual concentration of 80/140 mg (w/w).ConclusionThese findings demonstrated that the concentration of itopride in pharmaceutical samples using an established Partial Least Squares Regression calibration model can be determined with reliability.
Keywords: Itopride